MODULATION OF PHENOLICS SUBSTANCES AND ANTIOXIDANT ACTIVITY IN MANDAI CEMPEDAK BY UNSALTED SPONTANEOUS AND Lactobacillus casei INDUCED FERMENTATION - Anton Rahmadi; Kartika Sari; Frio Handayani; Yuliani Yuliani; Sulistyo Prabowo (Jurnal Teknologi dan Industri Pangan, 2019)
Cempedak (Artocarpus champeden) is a tropical fruit whose inner-skin contains high polyphenolic-based antioxidant. Traditionally, the inner-skin is soaked in brine to induce spontaneous lactic acid bacte-ria (LAB) fermentation. This research aimed to investigate the changes of polyphenolics substances and antioxidant activity during the course of spontaneous and Lactobacillus casei induced fermented at opti-mum (37°C) and sub-optimum (8°C) temperatures. Phenolic substances were spectrophotometrically measured with gallic acid (GAE), tannic acid (TAE), and catechin (CE) as the standards for the respective groups. The 50% maximum inhibitory concentration (IC50) for DPPH reduction was measured. A thin layer chromatography (TLC) using different solvents was utilized to qualitatively show differences of substances extracted from the unfermented and fermented mandai cempedak. The retention factor (Rf) values for TLC spots were measured after the plates were exposed under 366 and 254 nm of UV lamp. Fermentation increased phenolic substances release from the inner skin of cempedak which positively modulated the potential antioxidant activity. Sub-optimum temperature fermentation reduced total phenolic-based antioxidant. Ethyl acetate or combinations of n-hexane and ethyl acetate gave better separation in TLC plate. Differences in stain patterns were exhibited by mandai cempedak before and after L. casei induced fermentation. In summary, L. casei induced fermentation was more effective at optimum temperature to increase phytochemical substances of mandai cempedak, while spontaneous fermentation showed to be more effective after 11 and 13 days at sub-optimum temperature.